Obstacles to the Arab knowledge industry from the perspective of researchers at King Khalid University: - Al-Shahri, Norah Ali; Al-Shahri, Haya Mohammed (Journal of Humanities & Social Sciences, 2025)
The aim of this study was to identify the obstacles to dissemination of Arabic Knowledge from the perspective of researchers and proposing solutions to overcome obstacles to Arab knowledge rights, A modern technique was chosen that consisted of (61) male and female students from King Khalid University. (Bachelor's, master’s and PhD) for the year 2024-2025, The objectives were verified using the descriptive analytical approach. By distributing a survey consisting of (40) questions. The study was reached the following results: The Arab knowledge faces many obstacles, which are of a high level. which the cultural and societal obstacles came first, establishments obstacles came second, academic and personal obstacles came third, and scientific obstacles came last.The dissemination of Arabic knowledge faces many obstacles, some of which were at a high level. Administrative obstacles came first, and academic obstacles came in the second.One of the solutions to overcome the obstacles to knowledge and dissemination of Arab knowledge is to establish competitive periodicals with foreign journals. Providing access to data from its correct sources, increase funding for written Arabic research, lower costs of publishing in scientific journals, providing researchers with special skills in preparing research, providing sufficient research resources in Arabic, and supporting scientific publishing in various establishments.
Keywords: Knowledge; Arabic knowledge; researchers; King Khalid University